ANALISIS KESUKSESAN PRODUK MELALUI BRAND EXTENSION DIUKUR DARI MINAT BELI (Kasus Pada Merek Lifebuoy â€œShampoâ€ Di Kota Poso) - Lubalu, Adolf Ostaf Sovith (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2012)
Brand extension strategy does not always give satisfactory results. World- class companies also often fail in using the brand extension strategy. Brand extension has also been done by Lifebuoy to compete with other shampoo products. Carrying the name of the Unilever company andthephenomenalbrandLifebuoysoapbars,Lifebuoybrandextensionisapparentlyacceptable to the customer. Based on this phenomenon, this study aimed to analyze the success of the product through brand extension as measured by purchase intention.The model developed in this study involving six research variables including knowledge about the parent brand, company credibility, perceived quality on the brand extension, brand image of the extension, brand associations on the parent brand, and purchase intention of the brand extension. Data needed was obtained through interviews of 180 respondents who bought the Lifebuoy brand. Then, data is analyzed using Structural Equation Modelling (SEM).The test results show that knowledge about the parent brand proven to have a positive and significant influence on perceived quality of the brand extension, company credibility proven to have a positive and significant effect on perceived quality of the brand extensions, the statistics of company credibility proven to have a positive and significant impact on the parent brand associations, perceived quality of brand extensions are shown to have positive and significant effect on the image of the brand extension, brand image of the extension are shown to have positive and significant influence on purchase intention of the brandextension, the parent brand associations are shown to have positive and significant effect on the image of brand extensions and parent brand proven to have a positive and significant influence on purchase intention of the brand extension.